PENINGKATAN KETERAMPILAN MENULIS PUISI MELALUI PENERAPAN MODEL PICTURE AND PICTURE SISWA KELAS VIII SMP TRISAKTI AROEPALLA MAKASSAR - Hernita Arifuddin (Universitas Negeri Makassar, 2023)
The study aimed at analyzing (1) the learning implementation process of writing poetry using Picture and Picture model of class VIII students at SMP Trisakti Aroeppala Makassar, (2) the improvement of writing poetry learning result using Picture and Picture model of class VIII students at SMP Trisakti Aroeppala Makassar. The study employed classroom action research. The research data were in form of process data and result data. The result revealed thet after the implementation of Picture and Picture model were conducted in two cycles, the students in cycles I that 14 students (70%) was within the range of 2.66-3.33 in good category and 6 students (30%) was within the range of 1.66-2.32 in fair category. In cycle II, students score improved that 16 students (80%) was within the range of 3.66-4.00in excellent category and 4 students (29%) was within range of 2.66-3.33 in good category. In cycle II, the assessment of writing poetry skill of students had met the standard of Minimal Mastery Criteria used by the Bahasa Indonesia teachers in School, 2.66 therefore, the writing poetry skill learning usng Picture and Picture model to class VIII students at SMP Trisakti Aroeppala Makassar was confirmed as successful and showed significant improvement. Suggestion for students was to be more active in following the teaching and learning process, particularly in writing poetry learning; whereas, suggestion for teachers was they should employed Picture and Picture model in learning process of writing poetry.